2022
DOI: 10.1134/s0026893322050077
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Media in Studies of Cell Metabolism

Abstract: Changes in cell metabolism accompany the development of a wide spectrum of pathologies including cancer, autoimmune, and inflammatory diseases. Therefore, usage of inhibitors of metabolic enzymes are considered a promising strategy for the development of therapeutic agents. However, the investigation of cellular metabolism is hampered by the significant impact of culture media, which interfere with many cellular processes, thus making cellular models irrelevant. There are numerous reports that show that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Another limit of the study regards the use of RPMI medium for the experiments; although classical culture media such as RPMI have been extensively used in studies involving A2780 cells as well as other ovarian cancer cell models, recent studies have shown that the non-physiological concentration of some metabolites in their compositions impacts on cell physiology [51][52][53]. For example, in classical DMEM composition, glucose and pyruvate concentrations much exceed their normal concentrations in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Another limit of the study regards the use of RPMI medium for the experiments; although classical culture media such as RPMI have been extensively used in studies involving A2780 cells as well as other ovarian cancer cell models, recent studies have shown that the non-physiological concentration of some metabolites in their compositions impacts on cell physiology [51][52][53]. For example, in classical DMEM composition, glucose and pyruvate concentrations much exceed their normal concentrations in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports- have described that the usage of Plasmax media for culturing cancer cell lines may lead to an increase activity of the stress response transcription factor ATF4 (Hennequart et al 2021 ; Golikov et al 2022a , b ). Gardner et al claimed the importance of changing Plasmax media in a daily manner to never decrease nutrient concentrations below physiological levels, thus preventing a starving situation for cells that would cause ATF4 activation and compromise mTORC1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…1 B, C). While these ingredients promote cell growth, they do not precisely recapitulate the in vivo behavior of cells (Cantor 2019 ; Ackermann and Tardito 2019 ; Golikov et al 2022a ) and may have a great impact on studies of metabolic diseases. Recently, Human Plasma Like Media (HPLM) (Cantor et al 2017 ) and Plasmax media (Vande Voorde et al 2019 ) have been used to overtake commercial media flaws.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, to recapitulate the complexity and reality of metabolic features in patients, different research models have been employed other than cell lines, although they are technically easy to be handled with. The limitations by using cell lines in metabolism studies can be largely owing to (1) the culture conditions, such as the oxygen concentration, are totally different in laboratory in comparison to the real tumor; 75 (2) the geometry of cell culture is usually done in two-dimension layers, which is not able to mimic the three-dimensional, dynamic, and heterogeneous structure within the tumor; 76 (3) the cell culture media can vary significantly from the scenario of human blood or tumor microenvironment in terms of metabolite composition and concentration; 77 and (4) the rapid growth and proliferation of cell cultivation in vitro also impact the translation of findings. To overcome those technical obstacles, great efforts have been put to develop new study models that are more closely approximating the real conditions, thus providing more reliable metabolic results.…”
Section: Discussionmentioning
confidence: 99%